Mode Shift Model Simulation Due To The Operation Of Online Ojek (Case Study: Jalan Kebon Sirih, Central Jakarta) - Qonita Mahadi, Tamara
DKI Jakarta is one of the regions with severe traffic congestion due to the abundance of private vehicles on the road. The emergence of online motorcycle taxi in 2015 is hypothesized to shift people mode choice from non motorized and public transportation to online motorcycle taxi. One of the solutions to reduce traffic congestion is by promoting and facilitating traveler shift from online motorcycle taxi and private vehicle to public transportation. This research studied mode choice model and possibility of mode shifting to improve the level of service at Jalan Kebon Sirih, Central Jakarta. Using Multinomial Logit Model, this study found that mode punctuality, ownership of vehicle and parking availability were the deciding factors that always determine the utility of private vehicle whereas in-vehicle-time and mode convenience were the deciding factors for non private vehicle. From the developed utility model, it was known that the probability of choosing online motorcycle taxi was higher than private car and public transportation. This result did not conform to the purpose of reducing traffic congestion thus mode shift scenarios were developed so the probability of choosing public transportation increases while that for online motorcycle taxi and private vehicle decrease. The scenarios were developed using marginal effect analysis and were focused on variables that can improve the utility of public transport and reduce the utility of online motorcycle taxi and private car. Those variables were punctuality, in-vehicle-time, and convenience for online motorcycle taxi, convenience and in-vehicle-time for public transportation, and parking availability and vehicle ownership for private vehicle. The application of those scenarios can be done by decreasing the demand for transport or increasing the supply of transport services using the approach of traffic engineering or public policy. By using volume capacity ratio analysis it can be inferred that the implementation of the scenarios can upgrade road level of service until reaching the minimum level that was conditioned by Ministry of Transportation.